Advancing microfluidic point-of-care platelet function tests: opportunities and challenges from bench to market - Kang, Minki; Bresette, Christopher A.; Ku, David N. (Frontiers in Bioengineering and Biotechnology, 2024)
Platelets are critical for blood clotting, with shear-induced platelet aggregation (SIPA) playing a key role in hemostasis and the prevention of excessive bleeding. SIPA function potentially leads to life-threatening diseases such as hemorrhage and myocardial infarction, which are leading causes of death globally. Point-of-care platelet function tests (POC PFTs) are developed to assess platelet dysfunction and distinguish between normal and abnormal platelet activity. Recent advances in microfluidic technology have been integrated into POC PFTs, showing promise for delivering more accurate, rapid, and differentiated results using minimal blood sample volumes, enabling more informed treatment decisions. However, current POC PFTs fall short of replicating high-shear thrombotic conditions in vitro, resulting in limited clinical SIPA diagnosis and actionable insights. In this review, we explore the current landscape of POC PFT technology, key challenges, and future opportunities. We highlight the importance of device design and scalable manufacturing to fully realize the potential of microfluidic POC PFTs and facilitate their widespread adoption in clinical practice, ultimately improving patient outcomes.